Pengaruh Kualitas Produk Dan Harga Produk Terhadap Keputusan Pembelian Produk Pada UKM Maleo Lampung Timur: (Studi kasus pada UKM Maleo Lampung Timur) - Prambudi, Joko; Imantoro, Jati (Jurnal Manajemen DIVERSIFIKASI, 2021)
The development of the poultry business, namely floating birds, is increasingly making competition in this industry even tighter. So that the Maleo UKM business can be successful in the competition, must try to create and retain customers, so that this goal is achieved, the company must strive to produce goods and services that consumers want at affordable prices, thus, it must be able to understand consumer behavior on its target to increase product sales Maleo SMEs, because the survival of their business to meet the needs and desires of consumers is very dependent on these purchasing decisions. The research objective is to find out The Effect of Product Quality and Product Prices on Product Purchasing Decisions at Maleo UKM, East Lampung, this is done to solve the problem of how the business that has been run can continue to grow and run successfully in a competitive environment so that it can achieve the desired profit. This type of research used in research is quantitative research. The quantitative research method is one type of research whose specifications are systematic, well-planned and clearly structured from the start to the making of the research design. The results of the research on product quality have a significant effect on purchasing decisions in Maleo UKM, East Lampung. Product prices have no and insignificant effect on purchasing decisions at Maleo UKM, East Lampung. The quality of the product and the price of the product together have a significant and significant effect on the purchasing decision of the Maleo UKM, East Lampung.